EFFECTIVENESS OF ENFORCEMENT OF ADMINISTRATIVE SANCTIONS ON TENANTS IN THE INDUSTRIAL AREA AFTER REGULATION CHANGES - Rosi Liandani; Ade Maman Suherman; Tri Setiady; Wiwin Triyunarti (JCH (Jurnal Cendekia Hukum), 2026)
Enforcing environmental law in industrial areas is an important tool for preventing pollution and environmental damage from industrial activity. However, changes in regulations post-implementation, Constitution Number 6 of 2023 concerning Job Creation, and Government Number 22 of 2021 raise issues regarding the distribution of authority for supervising and implementing administrative sanctions against area tenants in the industry. Research this aim: analyse the authority manager area industry in a supervision environment, and evaluate the effectiveness of enforcement sanctions against area tenants in the industry. Research: This use-method study law normative with legislative, conceptual, and empirical (socio-legal) approaches. Research results show that the manager area industry basically has no independent authority for administrative sanctions. Because authority is authority, the public is only owned by the state administration. Conditions: This leads to a lack of authority and uncertainty in the practice supervision environment. In addition, the effectiveness of enforcement law is influenced by multiple interpretations of authority between government and managers, inconsistent enforcement mechanisms, limited supervisory capacity, lack of coordination between agencies and managers, and supervisory mechanisms that are not operating optimally. Therefore, it is necessary to clarify the distribution of regulatory authority and strengthen environmental supervision mechanisms to enhance the effectiveness of law enforcement in the industrial sector.